ANALISIS FUNDAMENTAL BERDASARKAN METODE PIOTROSKI F-SCORE GUNA PENILAIAN INVESTASI - Hiro Supranoto; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
This study was aimed to examine the effect of fundamental analysis based on the F-Score strategy toward the company stock return. F-Score is a measurement of the aggregate signal consisting of nine criteria to assess fundamental analysis. F-Score consist of return on assets (ROA), change in return on assets (ΔROA), cash flow from operation (CFO), accrual, change in leverage (Δleverage), change in liquidity (Δliquidity), change in equity (Δequity), change in gross margin ratio (Δmargin), dan change in assets turnover (Δturnover). The population of this study are companies listed in the LQ45 Index of Indonesia Stock Exchange in year 2016-2018. The samples were selected from non-financial companies registered in LQ45 Index within research period possess necessary data for the research using a purposive sampling. There are 29 companies that meet the criteria as research sample. Data analysis was performing by multiple linear regression analysis method. The results of this study showed that the value of the company’s F-Score has significant impact toward the stock return on companies listed in the LQ45 Index of Indonesia Stock Exchange. This study show that the company’s financial performance reflected in the annual report can be use for the basis invesment decision for investors.